Electrostatic adsorption and removal mechanism of ochratoxin A in wine via a positively charged nano-MgO microporous ceramic membrane. (1st March 2022) - Nan, Mi-Na; Bi, Yang; Qiang, Yao; Xue, Hua-Li; Yang, Lan; Feng, Li-Dan; Pu, Lu-Mei; Long, Hai-Tao; Prusky, Dov
Highlights: The first report on OTA removal with electrostatic adsorption by positive charged membrane. Positive charged nano MgO MCM was a cheap and efficient adsorbent with high OTA removal rate 91%. The removal mechanism was a spontaneous exothermic and non-specific physical adsorption process. Abstract: Ochratoxin A (OTA) is a very important mycotoxin. However, there are few studies on the removal of OTA in wine because of the great influence on product quality and difficulty in practical application. A nano-MgO-modified diatomite ceramic membrane (MCM) with a high positive charge was prepared and applied to remove OTA in wine. The isotherm adsorption between the positively charged membrane and OTA was in accordance with the Langmuir model, with a maximum adsorption capacity of 806 ng/g at 25 °C. All of the changes in adsorption enthalpy ( ΔH ), adsorption free energy ( ΔG ) and adsorption entropy ( ΔS ) were negative, which indicated that the combination of nano-MgO MCM and OTA was a spontaneous exothermic and nonspecific physical adsorption process. The concentrations of OTA in adsorption-treated wines were lower than 2 μg/kg, and the removal rates exceeded 92%. After OTA removal, the composition of wines was preserved to some extent.